Caracterização do processo de gelificação de soluções quitosana utilizando reometria e espalhamento dinâmico da luz - Morais, Wildson Arcanjo de (2011)
Gels consist of soft materials with vast use in several activities, such as in pharmaceutical industry, food science, and coatings/textile applications. In order to obtain these materials, the process of gelification, that can be physical (based on physical interactions) and/or chemical (based on covalent crosslinking), has to be carried out. In this work we used dynamic light scattering (DLS) and rheometry to monitor the covalent gelification of chitosan solutions by glutaraldehyde. Intensity correlation function (ICF) data was obtained from DLS and the exponential stretched Kohrausch-William-Watts function (KWW) was fitted to them. The parameters of the KWW equation, β, Γ and C were evaluated. These methods were effective in clarifying the process of sol-gel transition, with the emergence of non-ergodicity, and determining the range of gelation observed in about 10-20 minutes. The dependence between apparent viscosity on reaction time was used to support the discussion proposed.